The Good Research Guide : for small-scale social research projects - Denscombe, Martyn (Maidenhead : Open University Press, 2007)
This third edition offers guidance for success in small scale research projects, with new sections on ethics, Internet research, phenomenology, grounded theory and image-based methods.
Previous ed.: 2003.
Includes bibliographical references (p. 336-342) and index.
Keywords: Social sciences -- Research; Society